How? = 1/pi k [sin (k pi/2) – sin (k pi + k pi/2)] = 1/pi k [^2 cos (k pi/2 + k pi + k pi/2/2) sin (-k pi/2)]

91 2 - How? = 1/pi k [sin (k pi/2) - sin (k pi + k pi/2)] = 1/pi k [^2 cos (k pi/2 + k pi + k pi/2/2) sin (-k pi/2)]

This content is for Premium members only.
sign up for premium and access unlimited solutions for a month at just 5$(not renewed automatically)


images - How? = 1/pi k [sin (k pi/2) - sin (k pi + k pi/2)] = 1/pi k [^2 cos (k pi/2 + k pi + k pi/2/2) sin (-k pi/2)]

already a member please login